The Potential of Student-Authored Short Stories as Literary Readings in Schools: A Study on Creativity Levels - Huda, Miftakhul; Duerawee, Abdulkarim (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to explore the potential of short stories by students as literary reading in schools using the perspective of creativity level. This research uses an exploratory qualitative approach. The data of this study are verbal units that show the power of creativity in short stories. The verbal unit is in the form of in-text excerpts that represent creative elements in aspects of the originality of ideas, character development, innovation in plot, language exploration, and depth of theme. The creative element is an indicator of the level of creativity. The source of data for this research is 30 short stories by students of the Indonesian Language and Literature Education Study Program (PBSI) at FKIP UMS. Data collection is carried out through document analysis. Data analysis was carried out using Spiral Creswell. The results of this study show that students' short stories have considerable potential to be developed as literary reading in schools. Despite several weaknesses in the aspect of creativity, these works still show promising creativity. To improve the quality, students need to practice more in creating stories with more original ideas, building stronger plots, developing more complex characters, exploring themes more deeply, and enriching the use of language to make it more aesthetic and communicative. Thus, student short stories can serve not only as a medium of creative expression but also as a source of inspiring literary learning for students at school.